Neuronal Activity Related to Reward Size and Rewarded Target Position in Primate Supplementary Eye Field - Uchida, Yusuke (J Neurosci, 2007)
Several areas of the macaque brain are known to be related to the reward during the performance of saccadic eye-movement tasks. Neurons in the supplementary eye field (SEF) have been reported to be involved in the prediction and detection of a reward. We describe a group of neurons in the SEF that became active during the period of reward delivery after saccades toward a specific direction, but showed weaker activity in other directions, although the same amount of reward was given in each direction. Moreover, this directional reward activity was modulated by the reward size. Our results demonstrate that the SEF cells may reflect both reward amount and target positions toward which a movement was rewarded, and suggest that they may play an important role in providing information about the value of each saccade according to the spatial target location.